Gene Therapy: A Possible Alternative to CFTR Modulators? - Mercier, J.; Ruffin, M.; Corvol, H.; Guillot, L. (Frontiers in Pharmacology, 2021)
Cystic fibrosis (CF) is a rare genetic disease affecting several organs, but lung disease is the major cause of morbidity and mortality. The gene responsible for CF, the CFTR (Cystic Fibrosis Transmembrane Conductance Regulator) gene, has been discovered in 1989. Since then, gene therapy, i.e. the replacement of the defective gene by a functional version of this gene, remained the ultimate goal, but unfortunately it has not yet been achieved. However, patients care and symptomatic treatments considerably increased the life expectancy of CF patients ranging from 5 years old in the 1960s to 40 today. In the last decade, the development of new drugs readdressing CFTR to the plasma membrane (correctors) or enhancing its transport activity (potentiators), allow, alone or in combination, an improvement of CF patients lung function and quality of life. While expected, it is not yet known whether taking these drugs from an early age and for years will improve the quality of life of CF patients in the long term and further increase their life expectancy. However, these molecules are not available (specific variants of CFTR) and accessible (national health policies) for all patients and there is still no curative treatment. Other alternative that could benefit from new technologies, such as gene therapy, is therefore still attractive, although it is not yet offered to patients. Faced with the development of new CFTR correctors and potentiators, the question arises as to whether there is still a place for gene therapy and this is discussed in this perspective.